Integrating MAPK pathway inhibition into standard-of-care therapy for pediatric low-grade glioma - Crotty, Erin E.; Sato, Aimee A.; Abdelbaki, Mohamed S. (Frontiers in Oncology, 2025)
Pediatric low-grade gliomas (pLGG) are a group of tumors largely driven by alterations in a single genetic pathway, known as the RAS-RAF-mitogen-activated protein kinase (MAPK) pathway. Recent biologic insights and therapeutic targeting of MAPK-alterations have dramatically shifted the treatment approach in pLGG. While chemotherapy remains front-line therapy for unresectable pLGG in most scenarios (with the notable exception of BRAFV600E-altered tumors), many patients recur following cytotoxic agents and require further treatment. Inhibitors of the MAPK pathway, primarily MEK and RAF kinase inhibitors, have emerged as effective and tolerable second-line or later therapy for pLGG. As familiarity with these targeted agents increases, their indications for use continue to expand and Phase 3 clinical trials investigating their utility in the front-line setting are ongoing. We have adopted mitigation strategies for their associated toxicities; skin toxicity, in particular, is now managed by prevention strategies and early dermatologic intervention. This review highlights current approaches for the clinical implementation of MEK and RAF kinase inhibitors for pLGG, focusing on the practical aspects of drug administration, toxicity management, response monitoring, and distribution to patients experiencing geographic or financial barriers to care. Additionally, we review important considerations for the off-label use of these agents while contemporaneous clinical trials assessing front-line efficacy are ongoing. We discuss the potential for more expansive or histology-agnostic tumor targeting using MEK inhibitors, harnessing their biologic relevance for other RAS-altered conditions.